Cell adhesion and proliferation onto chitosan-based membranes treated by plasma surface modification - Luna, Sandra M. (2011)
Surface properties play a vita role in the functioning of a biomaterial. Cellular adherence and growth onto biomaterials can be enhanced in biomaterial modifications of their surface. In this work, the cell behaviour on chitosan membranes modified by argon and nitron-plasma treatments was investigated. Characterization of the membranes was performed using atomic force microscopy, contact angle measurements, and X-ray photoelectron spectroscopy. Cytotoxicity assessment and direct contact assay were carried out for untreated and treated chitosan membranes using L929 fibroblast-like cells. Cell morphology and cell viability were assessed to evaluate the cell attachment and proliferation. Changes in terms of roughness, surface chemistry, and hydrophilicity/hydrophobic balance of chitosan-modified membranes were observed. Regarding cell studies, the findings revealed that the extracts of all membranes do not induce cytotoxicity effects. Moreover, the in vitro assays evidenced an improvement of the L929 adhesion, and attachment when compared to untreated chitosan membranes. overall, the data obtained clearly demonstrated that plasma treatments constitute an effective way of improving the biocompatibility of chitosan membranes towards to their use in biomedical applications.